PENGARUH TELEVISYEN TERHADAP GOLONGAN KANAK-KANAK DI PERINGKAT SEKOLAH RENDAH: KAJIAN KES DI KALANGAN KANAK-KANAK SEKOLAH RENDAH KEBANGSAAN ST. JOSEPH DAN SEKOLAH RENDAH KEBANGASAAN ST. TERESA, KUCHING, SARAWAK - Norazreen, Sapiee (Universiti Malaysia Sarawak, (UNIMAS), 2005)
The aim of this study is to examine the influence of television towards primary school students in Sekolah Rendah Kebangsaan St. Joseph and Sekolah Rendah Kebangsaan St. Teresa, Kuching, Sarawak. Two hundred respondents were chosen as samples in this research. The respondents were asked to give their opinion on the influence of television based on the time they spend watching television, their behaviour, the way they dress up, their knowledge, how they spend their free time and type of programme that they like most. Analysis of data was done by using frequency and crosstab methods. The results showed that there were significant relationships between the time the students spend on watching television, especially boys, and their behavior, the way they dress up and how they spend their free time. Besides that, the results also showed that the type of programme that the students like are mostly violence and love story. Thus, majority of the students age 12 from both school sad that they do not like religious and educational programme.